PENGARUH CITRA MEREK DAN TERPAAN IKLAN MEDIA LUAR RUANG GOJEK TERHADAP TINGKAT AWARENESS GOJEK DI MAHASISWA UNDIP - Rahmadianto, Rizky; Luqman, Yanuar; Setyabudi, Djoko (Interaksi Online, 2024)
This research aims to examine and understand the influence of Gojek's brand image and outdoor media exposure on the level of Gojek awareness among students of Diponegoro University (Undip). The research method utilizes an explanatory quantitative approach with the population of individual Gojek application users and active Undip students. A sample of 124 people was selected using nonprobability sampling techniques, and primary data was collected through questionnaires. Data analysis employed simple linearregression to measure the relationship between brand image, outdoor media exposure, and Gojek awareness level among Undip students. In conclusion, this research has successfully demonstrated the significant influence of Gojek'sbrand image and outdoor media exposure on the level of Gojek awareness among Undip students. The research findings, with significance values in the simple linearregression test of 0.030 and <0.01 for each variable, underscore the importance of brand image and outdoor advertising exposure in shaping Gojek awareness among Undip students. Therefore, it is recommended that Gojek enhance its outdoor media exposure to improve its brand image andGojek awareness among Undip students